Iron overload causes endolysosomal deficits modulated by NAADP-regulated 2-pore channels and RAB7A. Issue 9 (1st September 2016) - Fernández, Belén; Fdez, Elena; Gómez-Suaga, Patricia; Gil, Fernando; Molina-Villalba, Isabel; Ferrer, Isidro; Patel, Sandip; Churchill, Grant C.; Hilfiker, Sabine
ABSTRACT: Various neurodegenerative disorders are associated with increased brain iron content. Iron is known to cause oxidative stress, which concomitantly promotes cell death. Whereas endolysosomes are known to serve as intracellular iron storage organelles, the consequences of increased iron on endolysosomal functioning, and effects on cell viability upon modulation of endolysosomal iron release remain largely unknown. Here, we show that increasing intracellular iron causes endolysosomal alterations associated with impaired autophagic clearance of intracellular protein aggregates, increased cytosolic oxidative stress and increased cell death. These effects are subject to regulation by NAADP, a potent second messenger reported to target endolysosomal TPCNs (2-pore channels). Consistent with endolysosomal iron storage, cytosolic iron levels are modulated by NAADP, and increased cytosolic iron is detected when overexpressing active, but not inactive TPCNs, indicating that these channels can modulate endolysosomal iron release. Cell death triggered by altered intralysosomal iron handling is abrogated in the presence of an NAADP antagonist or when inhibiting RAB7A activity. Taken together, our results suggest that increased endolysosomal iron causes cell death associated with increased cytosolic oxidative stress as well as autophagic impairments, and these effects are subject to modulation by endolysosomal ion channel activity in a RAB7A-dependent manner. These data highlight alternative therapeutic strategies for neurodegenerative disorders associated with increased intracellular iron load.